Reflections upon the analysis of foundation manifestos by Unión Democrática and the Peronist Party in La Pampa (1945-1947) (Quinto Sol, 2013)
Through the analysis of foundation manifestos of  La Junta Pro Unión Democrática and La Junta Territorial del Partido Peronista in La Pampa we study the relationship of adequacy and difference between the issues posed in the discursive level and the concrete needs and situations of pampean society by the mid 1940´s. An analysis is made concerning real dimensions of the impact of interpellations contained in those texts upon the population of the Territory, taking into account the long-term exclusion of such jurisdictions as regards national politics and their reach in the building of citizenship. In the social rights level, some sectors of pampean society, like workers, were benefited in a real and inmediate way with peronist policies, consequently identifying themselves with social and economic claims announced in the manifesto. However, from the point of view of political rights, differently from the provinces and except for the case of women, the process was incomplete. Not until the first years of the 1950 decade would La Pampa enjoy full citizenship in which it would effectively feel itself as part of the national state.
Keywords: Peronism; Democratic Union; national territories; citizenship